The relationship between polycystic ovary syndrome and gynecological cancers: neurotransmitter metabolism changes and immune regulation - Wu, Dongning; Zhang, Yue; Wu, Congying; An, Bo; Wang, Xin; Ni, Jinxia; Chen, Min (Frontiers in Immunology, 2025)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting approximately 10% of middle-aged women worldwide. It is characterized by hirsutism, anovulation, and polycystic ovaries. Various factors, including environmental toxins, inflammation, oxidative stress, and insulin resistance, contribute to the progression of this condition. PCOS is also associated with metabolic disturbances, such as abnormal hormone and neurotransmitter metabolism, leading to obesity, hyperandrogenemia, and type 2 diabetes. Among female cancers, breast cancer, endometrial cancer, and ovarian cancer have high incidence rates and pose significant threats to women’s health. Studies suggest a potential link between PCOS and these gynecological cancers. Consequently, hormonal alterations in PCOS patients may influence tumorigenesis and metastasis. Moreover, PCOS is characterized by chronic low-grade inflammation, including dysregulated pro-inflammatory cytokine secretion, increased immune cell proliferation, and endothelial dysfunction. These factors contribute to cancer development, primarily through impaired immune metabolism, preventing effective tumor cell clearance and facilitating metastasis. This review synthesizes current knowledge on the mechanistic links between PCOS and gynecological cancers, focusing on the roles of immune cell dysfunction, aberrant cytokine secretion, and neurotransmitter metabolism. Therapeutic strategies, including hormonal interventions, insulin sensitizers, and lifestyle modifications, may mitigate cancer risk by modulating these pathways. This review highlights critical gaps in understanding PCOS-related oncogenesis and advocates for further research to elucidate molecular mechanisms and optimize clinical management.